Money Demand in the Euro Area : Where Do We Stand (Today)? - Kontolemis, Zenon (IMF Working Papers; Working Paper ;, 2002)
The paper reviews the stability of long-run money demand in the euro area in the light of recent revisions to M3 data. The analysis confirms the existence of a stable long-run money demand, although the estimated equation implies a smaller equilibrium M3 growth than the European Central Bank's reference value of 4 1\2 percent. The stability of long-run money demand does not imply that the market is always in equilibrium. Indeed, it is argued that periods of disequilibrium can be long and adjustment slow. The paper shows that the difference between the low estimated equilibrium growth rate and the actual growth rate for M3 can be explained by a velocity shock, identified here as the sharp fall in equity prices in the last two years. These characteristics of the money market-summarized in the events of the last two years-would call for an alternative approach in the communication of monetary policy developments, essentially putting less emphasis on month-to-month developments in M3.